Piezoelectric material characterization by acoustic methods - LE CLEZIO, Emmanuel; DELAUNAY, Thomas; LAM, Mountaga; FEUILLARD, Guy (Archives of Acoustics, 2008)
Two characterization methods of piezoelectric materials based on acoustic measurements are presented. Their main objective is to identify the entire set of electromechanical properties of piezoelectric materials from a single sample. In order to characterize new materials like single-crystals with small dimensions, the first section of the paper presents an identiffication protocol based on the study of the resonance spectra of parallelepipeds. The second characterization method is performed by means of the measurement of the transmission coefficients of plane waves propagating through an immersed plate. It is is suitable for the determination of the properties of bulk piezoelectric ceramics.